Reconstructing, monitoring, and predicting multidecadal-scale changes in the North Atlantic thermohaline circulation with sea surface temperature - Latif, Mojib; Roeckner, E.; Botzet, M.; Esch, M.; Haak, H.; Hagemann, S.; Jungclaus, J.; Legutke, S.; Marsland, S.; Mikolajewicz, U.; Mitchell, J. (AMS (American Meteorological Society), 2004)
Sea surface temperature (SST) observations in the North Atlantic indicate the existence of strong multidecadal variability with a unique spatial structure. It is shown by means of a new global climate model, which does not employ flux adjustments, that the multidecadal SST variability is closely related to variations in the North Atlantic thermohaline circulation (THC). The close correspondence between the North Atlantic SST and THC variabilities allows, in conjunction with the dynamical inertia of the THC, for the prediction of the slowly varying component of the North Atlantic climate system. It is shown additionally that past variations of the North Atlantic THC can be reconstructed from a simple North Atlantic SST index and that future, anthropogenically forced changes in the THC can be easily monitored by observing SSTs. The latter is confirmed by another state-of-the-art global climate model. Finally, the strong multidecadal variability may mask an anthropogenic signal in the North Atlantic for some decades.